2015
DOI: 10.3389/fpls.2015.00539
|View full text |Cite
|
Sign up to set email alerts
|

Camalexin contributes to the partial resistance of Arabidopsis thaliana to the biotrophic soilborne protist Plasmodiophora brassicae

Abstract: Camalexin has been reported to play defensive functions against several pathogens in Arabidopsis. In this study, we investigated the possible role of camalexin accumulation in two Arabidopsis genotypes with different levels of basal resistance to the compatible eH strain of the clubroot agent Plasmodiophora brassicae. Camalexin biosynthesis was induced in infected roots of both Col-0 (susceptible) and Bur-0 (partially resistant) accessions during the secondary phase of infection. However, the level of accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The IAOx pathway is Brassica specific and can produce three types of active compounds: camalexin, indole glucosinolates, and indole-3-acetic acid (Hull et al, 2000;Zhao et al, 2002;Mikkelsen et al, 2000;Glawischnig et al, 2004;Sugawara et al, 2009). Both camalexin and indole glucosinolates act as defense compounds induced in both shoot and root upon pathogen attack (Glawischnig, 2007;Halkier and Gershenzon, 2006;Brown et al, 2003;Lemarié et al, 2015), but no clear link to root development has been found. The IAOx pathway has been shown to contribute to auxin production under heat stress conditions (Zhao et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The IAOx pathway is Brassica specific and can produce three types of active compounds: camalexin, indole glucosinolates, and indole-3-acetic acid (Hull et al, 2000;Zhao et al, 2002;Mikkelsen et al, 2000;Glawischnig et al, 2004;Sugawara et al, 2009). Both camalexin and indole glucosinolates act as defense compounds induced in both shoot and root upon pathogen attack (Glawischnig, 2007;Halkier and Gershenzon, 2006;Brown et al, 2003;Lemarié et al, 2015), but no clear link to root development has been found. The IAOx pathway has been shown to contribute to auxin production under heat stress conditions (Zhao et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the reduction in tryptophan is contrary to the upregulation of genes within the tryptophan biosynthetic pathway (Figure 4). The observed decrease in the tryptophan level may be due to a potential increase in the biosynthesis of the tryptophan-derived antimicrobial phytoalexin, camalexin (Lemarié et al, 2015), through the dramatic increases in both RS and RF (66-fold) of the key camalexin biosynthetic enzyme, tryptophan N-monooxygenase, CYP79B2 (EC 1.14.14.156; Figure 4 and Supplemental Figure 7A). Moreover, the CYP79B2 mRNA had a slight increase of ribosomal association upon ETI induction in the ribosome pelleting experiment, suggesting a potential contribution of translational regulation (Supplemental Figure 7B).…”
Section: Dynamics Of Amino Acid Metabolism During Etimentioning
confidence: 99%
“…Phosphinothricin-resistant primary transformants were confirmed by PCR and qualitatively screened for GFP fluorescence in response to AgNO 3 spraying. A high-expression line was crossed to the cyp71b15/pad3 T-DNA insertion line SALK_026585 (Xu et al, 2008;Lemarié et al, 2015), and homozygous pad3/CYP71B15 pro :CYP71B15-GFP plants that carried the construct and (at least partially) complemented the camalexin-deficient pad3 phenotype were selected from the F2 generation (Supplemental Figure 1B). The progeny of one individual was used for proteomics analysis.…”
Section: Generation Of Transgenic Arabidopsis Linesmentioning
confidence: 99%